Optimization of culture conditions to improve the expression level of beta1–epsilon toxin of Clostridium perfringens type B in Escherichia coli. Issue 2 (3rd March 2016) - Lin, Chuwen; Cheng, Likun; Wang, Jing; Zhang, Songlin; Fu, Qiang; Li, Shuguang; Li, Feng; Han, Wenyu; Shen, Zhiqiang
ABSTRACT: The detoxified beta1–epsilon (β1–ϵ) toxin protein of Clostridium perfringens type B provides protection from C. perfringens types B, C and D infections. Acetate is the primary by-product from the cell growth and expression of β1–ϵ protein. In the present study, the effects of pH and dissolved oxygen (DO) on the expression of β1–ϵ protein were investigated. Two-stage pH and DO control strategies were developed for the expression of β1–ϵ protein. The obtained results indicated that higher cell density and concentration of β1–ϵ protein, and lower accumulation of acetate were obtained when pH was maintained at a constant level of 6.5 (0–6 h) and 7.0 (6–16 h), and the DO level was maintained at 60% (0–6 h) and 30% (6–16 h). Furthermore, the impact of intermittent, DO feedback, pH feedback and glucose-stat feeding on the expression of β1–ϵ protein were studied. By using the DO feedback feeding, combined with the stage control of pH (6.5 for 0–6 h, 7.0 for 6–16 h) and DO (60% for 0–6 h, 30% for 6–16 h), the highest cell density of 2.045 (absorbance at 600 nm) and a β1–ϵ protein concentration of 63.24 mg/L were obtained, and the accumulation of acetate decreased to 0.872 g/L.